Dentists' decision strategies for suspicious occlusal caries lesions in a National Dental PBRN study. (February 2018) - Makhija, Sonia K.; Robinson, Michael E.; Bader, James D.; Shugars, Daniel A.; Litaker, Mark S.; Im, Hong R.; Rindal, D.Brad; Pihlstrom, Daniel J.; Meyerowitz, Cyril; Gordan, Valeria V.; Buchberg, Meredith K.; Gilbert, Gregg H.; et al.
Abstract: Objective: Case presentations (vignettes) were completed by dentists in the National Dental Practice-Based Research Network study "Decision Aids for the Management of Suspicious Occlusal Caries Lesions (SOCLs)". The objective was to determine dentists' decision strategies for SOCLs. Methods: 107 dentists viewed a series of 16 vignettes that represented all combinations of 4 clinical cues: color, luster, lesion roughness, and patient-level caries risk. Each vignette included a patient description and a photograph of a tooth presenting the 4 cues. Dentists were asked to decide the likelihood that a suspected lesion extended into dentin. A lens model analysis was used to examine how dentists use these cues in making their decisions. Results: 86% of dentists had a consistent pattern of cue use that defined their decision strategy. On average, 70% of the variance in their decisions was accounted for by their use of the 4 cues. However, there was considerable variability in the individual cues used by each dentist. The percentages of dentists who used the different cues consistently were: luster (58%), color (48%), roughness (36%), and risk (35%). 14% of dentists reliably used only color, 7% used only luster, 4% used only roughness, and 1% used only risk when making SOCL decisions. Conclusions: The online vignette system suggests that clinical SOCL decision strategies are highly individualized and dentists do not use all cues available to them to make these decisions. Clinical significance: Prior to this study, there has been little evidence about how dentists use these cues (either individually or in combination) when judging the extent of caries progression. Such knowledge would be valuable when designing interventions to help dentists maximize the likelihood of appropriate treatment decisions.